Failure Mechanisms of Structural Bamboo Using Microstructural Analyses - Mutaz K. Chahrour; Md. Akter Hosen; Yingxin Goh; Teong Yen Tong; Soon Poh Yap; Mohamed Amine Khadimallah (Advances in Materials Science and Engineering)
Bamboo is deemed an emerging constructional material with promising application projections due to the reliable natural properties and advantageous structural characteristics. However, there is a lack of systematic studies on the mechanical characteristics of the bamboo species from a microstructural scale. Hence, this paper investigated the primary mechanical properties of the bamboo specimens (Dendrocalamus asper) with further microstructural analysis on the bamboo failure. The direct tensile strength of bamboo specimens was about 226.45 MPa, while the final splitting tensile modulus was found to be 2.88 MPa. Microstructural characterisation of the failed tensile specimens indicates that fibre debonding is the main failure mechanism under tensile conditions. On the other hand, splitting and end bearing failure were found on compression test specimens. In addition, nanoindentation tests were carried out on different cell structures to articulate the hardness and Young’s modulus. The elastic modulus of the fibre cell walls is three times that of the parenchyma cell walls, yet the hardness values are comparable. This confirms that the specimen failure of previous macromechanical testing is due to crack propagation along the parenchyma cells, instead of the cell walls. Based on the experimental studies discussed in this paper, the conclusion can convey a positive message regarding the ability of bamboo as a primary sustainable substitute for conventional construction materials.